Comparing isogenic strains of Beijing genotype Mycobacterium tuberculosis after acquisition of Isoniazid resistance: A proteomics approach - Nieto R, Luisa María (Proteomics, 2016)
We determined differences in the protein abundance among two isogenic strains of Mycobacterium tuberculosis (Mtb) with different Isoniazid (INH) susceptibility profiles. The strains were isolated from a pulmonary tuberculosis patient before and after drug treatment. LC‐MS/MS analysis identified 46 Mtb proteins with altered abundance after INH resistance acquisition. Protein abundance comparisons were done evaluating the different bacterial cellular fractions (membrane, cytosol, cell wall and secreted proteins). MS data have been deposited to the ProteomeXchange with identifier PXD002986.